Work of Sir Robert Lorimer - Savage, Peter D. (The University of Edinburgh, 1973)
This thesis provides a chronological account of Lorimer's career and his work in eight chapters. The aim is to show how his work developed during his lifetime. The opportunities he was able to grasp, and his achievements in building design and landscaping are discussed. The second, allied, aim of this thesis is to show how Lorimer's abilities developed within the three different roles which he assumed at the professional level. The first two chapters discuss his development in early years; chapters 3, 4 and 5 discuss his middle years as a private architect, mainly for domestic buildings; chapter 6 discusses his role as a principal architect for the Imperial War Graves Commission, for which he acted in a public role; chapter 7 discusses the Scottish National War Memorial, for which he acted as National Architect. Lorimer's work is appraised at each stage in his career, and the fact that he enjoyed several different reputations in his own lifetime is discussed. Whereas he was seen as a pioneer at the end of the last century, by the end of the first decade of this century he was widely known as a Gothicist. His country houses then gained him the reputation of being the Scottish Lutyens, and finally in the thirties, the Scottish National War Memorial evoked a national pride so intense that it confirmed Lorimer more as a patriot than as any particular caste of architect.
An examination of the work of Sir Robert Lorimer
Keywords: Scottish architect